Prediction of the Long-Term Tensile Strength of GFRP Bars in Concrete - Peng Zhu; Zongyang Li; Yunming Zhu; Yuching Wu; Wenjun Qu (Buildings, 2023)
The durability of two types of widely used glass fiber reinforced polymer (GFRP) bars, one without coating (G1) and one with slightly surface sand-coating (G2), were studied through accelerated aging. Concrete cylinders reinforced with GFRP bars were immersed in tap water in temperature-controlled tanks. The influence of different exposure temperatures, 20, 40, and 60 °C, and also different exposure times, 30, 60, 90, 120, and 180 days, on the degradation of the two types of GFRP bars was investigated. The tensile strengths of GFRP bars after different exposure times were evaluated with tensile tests, and the variation of the microstructure and elemental compositions of conditioned specimens was evaluated with scanning electron microscopy (SEM) images and energy dispersive X-ray spectroscopy (EDS), respectively. The degradation rate of the tensile strength retentions of two types of GFRP bars decreased with an increase in the exposure time at all exposure temperatures. The tensile strength retentions of the GFRP bars were studied by three commonly used prediction models. Based on the degradation mechanism of fiber-matrix debonding, a new model was proposed. These four models were evaluated with the test results and a new model proposed was suggested as the best model to predict the residual tensile strength of the GFRP bars. The durability parameters of the GFRP bars were discussed. The tensile strength retention tended to converge to a constant value (52%) with the increase of exposure time, which contributes to the determination of the environmental reduction factor in relevant design guides, and the fiber-matrix debonding was found to be the main degradation mechanism due to the surrounding concrete environment. The sand-coating had some effect on the activation energy of the GFRP bars.